Pengaruh Penerapan Cashless Payment terhadap Perilaku Penerimaan E-Samsat berdasarkan Pendekatan Technology Acceptance Model - Reffi Trinovayanti Purwanto; Riauli Susilawaty Hutapea; Usmani (Indonesian Accounting Research Journal, 2021)
To increase participation in the payment of Vehicle Tax (PKB), the West Java Provincial Government implements cashless payment by creating an E-Samsat Jabar, one of the payments can using Bank ATMs. In reality, there are still obstacles because the user still find it difficults. The research purposes is to find out how the acceptance of E-Samsat in the implementation of cashless payment with Technology Acceptance Model (TAM). The research methods is descriptive quantitative. The sampling technique is purposive sampling and resulted 10 Districts/City in West Java Province as sample. The analyzed model using SEM-PLS with SmartPLS. The results of this research shows Perceived Ease of Use has proven to influence Perceived Usefulness and Attitude Towards Using, Perceived Usefulness has proven to influence Attitude Towards Using, and Attitude Towards Using has proven to influence Acceptance of E-Samsat. And also prove that Perceived Usefulness has not influence the Acceptance of E-Samsat.